DEVELOPMENT OF THE MODEL OF COMPETENCE: APPROACHES AND IMPLEMENTATION - I. Ivanov; T. Lukyanova (Вестник университета)
The analysis of the concept of “competence” has been made. The stages of building a competency model for an accountant performing consulting functions based on a judgement-based approach have been described. A step-by-step development of an accountant’s competency model has been carried out (the existing performance of functions was assessed, and the desired performance has been described; the competencies necessary for the successful performance of their functions were determined; the behavioral indicators have been distributed according to competences; finally the original competence model of the accountant of the organization has been formed).